Effect of fibre hydrolytic enzymes supplementation on performances of broiler chickens fed diets containing rice bran - Pius P Ketaren; T Purwadaria; A.P Sinurat; T Haryati (Indonesian Center for Animal Research and Development (ICARD), 2012)
Use of the rice bran as poultry feed is restricted by its high fibre content as poultry is unable to hydrolyse the fibre into available energy. This experiment was aimed The aim of this experiment was to investigate the effect of crude enzymes supplementation on performances of broiler chickens fed diets containing 30% rice bran. The experiment was based on completely randomized design with nine experimental diets. Diets 1-5 contained 5% less than recommended protein and energy, based on determined metabolizable energy (ME) content in the rice bran at 2040 kcal/kg, without taking into account on the beneficial effect of the enzyme supplementation. These diets were: 1. A control diet (D2040, without enzymes); 2. D2040 + E. javanicum (BS4) + P. nalgiovense (S11); 3. D2040 + BS4 + A. niger; 4. D2040 + BS4 + commercial enzymes (CE); 5. D2040 + B. pumilus (PU4-2) + CE. Four other experimental diets contained the same protein and energy levels as in the diets 1-5, but had taken into account on the beneficial effect of the enzyme supplementation,. These diets were: 6. D2702 + BS4 + S11; 7. D2650 + BS4 + A. niger; 8. D2465 + BS4 + CE ;and 9. D2465 + PU4-2+ CE. Each experimental diet was repeated six times and each replication consists of 5 day-old broiler chickens. Results showed that FCR of the chickens fed D2040 + PU4-2 + CE diet (FCR = 1.38) and D2465 + PU4-2 + CE diet (FCR = 1.46) were significantly (P < 0.01) improved compared to the control diet (FCR = 1.64). This experiment strongly shows that supplementation of PU4-2 + CE enzymes significantly (P < 0.01) improved feed efficiency of the broiler chickens by 11-16%. Key Words: Fibre Hydrolytic Enzymes, Broiler Chickens, Performances